Yield response of soybean (Glycine max) and wheat (Triticum aestivum) to potassium and changes of potassium status in soil after long-term sequential cropping - PRAKASH, VED; KUNDU, S; GHOSH, B N; SINGH, R D; GUPTA, H S (The Indian Journal of Agricultural Sciences, 2014)
A long-term field study was carried out during 2000 to assess the yield response of soybean [Glycine max (L.) Merr.] and wheat (Triticum aestivum L. emend. Fiori & Paol.) to K application in relation to advancing years of cropping, changes in K status in soil profile and to estimate the contribution of non-exchangeable K to crop uptake. Average yield data of 27 years showed significant response to applied K, resulting in 69.9% increase in yield of soybean and 20.0% increase in residual wheat crop. Year-wise yield response pattern exhibited gradual increase in K response with the advancing years. During 1973-79 and 1986-96, average yield response of soybean ranged from 7.22 to 11.7 kg seed/kg K and 22.71 to 25.73 kg seed/kg K respectively. The yield response of succeeding wheat to residual K also showed increasing trend from 2.42 to 4.77 kg seed/kg K during 1973-80 to 8.10-9.65 kg seed/kg K during 1985-93. After 27-year crop cycle, total removal of K by the crops exceeded K applied to the soil, showing a net negative K balance, ranging from 73.9 to 937.3 kglha. Soil analysis after 27 years of cropping, showed net depletion of K in the soil profile (0-45 cm) with varying magnitudes, depending on the yield responses to applied fertilizers and manurial inputs. Continuous annual application of recommended doses of NPK and 10 tonnes farmyard manure to soybean sustained not only higher productivity of soybean and residual wheat crop, but also resulted in build-up of available K (26.7 kg K/ha) and relatively lower crop mining of K from non-exchangeable pool (595.3 kg K/ha). In the treatments receiving NP or NPK, non-exchangeable K contributed 96.25 and 49.02% of total crop removal respectively. However, the contribution of non-exchangeable K decreased substantially to 19.3 8% in the treatment receiving continuous application of recommended doses of NPK and 10 tonnes of farmyard manure/ha.